Dampak Kekerasan Dalam Rumah Tangga Terhadap Penegakan Keadilan: Persfektif Asas Korektif, Rehabilitatif dan Restoratif - Anwar, Reski; Mardalena, Mardalena; Lintang, Ayu; Hidayat, Taufik (Fakultas Syariah dan Ekonomi Islam, IAIN Syaikh Abdurrahman Siddik, Bangka Belitung, 2024)
Abstract: Violence is an act that causes pain or suffering, either directly or indirectly, to another person. Meanwhile, domestic violence is categorized as criminal behavior that has a negative impact on the victim; These adverse impacts may be physical, mental or psychological. Due to the negative impacts caused by this law and the large number of cases that frequently occur, a law has been developed that can regulate the eradication of this problem. This written study carried out a literary study. The research methodology implements a normative legal approach because research is not committed to discussing the implementation of regulations and the implementation carried out is a qualitative approach by collecting information from books and journals. Domestic violence (KDRT) is something that often occurs in social violence, where this violence is universal in nature because it can occur within a household without the division of culture, religion, national culture, and the nature of the perpetrators and the victims. Because of this, it can occur in households of ordinary, poor and remote families as well as households of rich, educated, well-known and prominent families. This means that here violence emerges as a result of each individual's personality without thinking in a healthy manner and a high level of egoism, the domestic violence criminal law regulates other ways of racial justice in the criminal law law book which not only regulates prison sentences and criminal law, that is, it can result in criminal wrongdoing. social and justice restoration programs implemented against someone who has committed an evil act. This is intended so that perpetrators do not carry out things that are completely despicable. Keywords: Violence Domestic, Perpetrators, Victims, Justice.